Fa`āliyatu Ṭarīqati Balāgān fī Ta`līmi al-Qawā`idi al-Naḥwiyyati bi Ma`hadi Bandūnj al-Garbiyyati - Ahyarudin Ahyarudin; Willy Hardicky (ALSUNIYAT: Jurnal Penelitian Bahasa, Sastra, dan Budaya Arab, 2022)
This research aims to discover the balagan method's concept in teaching grammar rules at the Institute of Jihad Bandung West. Moreover, how to implement the balagan method in teaching grammar rules at the Institute of Jihad Bandung West. Find out how effective the balagan method is in teaching grammar at the Jihad Institute of Western Bandung. The approach used by the researcher in completing this research is the descriptive analysis method, and the type of this research is field research. The researcher identified the problem, developed hypotheses, collected data, and information, then analyzed and interpreted them and thus reached conclusions and recommendations. After the researchers conducted and delved deeper into the reflection of the balagan method used at the Jihad Institute of Western Bandung, the researchers concluded that the balagan method helps students develop language skills. This method is appropriate to be applied in the Institute of Jihad Bandung West and another institute in most students, and it is known that the last percentage of these studies indicates this. In order, they are 76%, 22%, 2% or "no" answered "yes", "neutral" and "no".